Educational aspects of rare and orphan lung diseases - Alfaro, Tiago M.; Wijsenbeek, Marlies S.; Powell, Pippa; Stolz, Daiana; Hurst, John R.; Kreuter, Michael; Moor, Catharina C. (Respiratory research, 2021)
People with rare lung diseases often suffer the burden of delayed diagnosis, limited treatment options, and difficulties in finding expert physicians. One of the reasons for the delay in diagnosis is the limited training for healthcare practitioners on rare diseases. This review explores the main concerns and needs for education on rare lung diseases from the perspectives of both patients and professionals. Despite the increasing interest in rare lung disorders and some recent breakthrough developments on the management of several diseases, healthcare professionals, including general practitioners and hospital workers, receive little education on this topic. Nonetheless, many healthcare professionals show much interest in receiving further training, especially on diagnosis. Patients and families want easier access to high-quality education materials to help them manage their own disease. Well-educated patients are better equipped to deal with chronic diseases, but patient education can be challenging as patients’ individual health issues, and diverse backgrounds can create significant barriers. Raising more awareness for rare lung diseases and further development of patient-centred international expert networks like the European Reference Network on Rare Lung Diseases (ERN-LUNG), which includes both experts and patient representatives, are essential for improving care and education on rare lung diseases. Initiatives such as the Rare Disease Day, have been successful in increasing awareness for rare conditions. The development of online tools for accessing information has had positive effects and should be further supported and extended in the future.
Gesehen am 20.04.2021